Depression and suicide in doctors in Brazil: an integrative review 2013-2021 (Research, Society and Development, 2022)
Depression or major depressive disorder is characterized by the presence of physical and mental symptoms that compromise decision-making and attitudes. According to the World Health Organization, depression is the cause of 800,000 suicides a year. Suicide is ending one's life. There is a high and growing prevalence of psychiatric illnesses in professions such as medicine, with inner and social compromises and low quality of life, making them a public health problem. This is an integrative review on depression and suicide in physicians in Brazil, with the keywords "depression", "suicide", "physician" and "prevention", carried out in databases in the LILACS, PubMed and Scielo databases in the period from 2013 to 2021. The final sample consisted of seven articles, where there was a relationship between depression and suicide with workload, job satisfaction and valorization, sleep disorders, physical activity, social isolation and alcohol abuse. It is concluded that the imbalance of these factors predisposes to a high prevalence rate of depression and suicide in Brazil, and that there is a need for an increase in the number of studies and deepening around this theme.